ANALISIS PERKEMBANGAN DAN KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI KOTA SEMARANG (Students' Journal of Accounting and Banking, 2015)
The research purposes to determine the progress and contribution or taxes and levies for local revenue (PAD) in Semarang City. The population is all of reception data of taxes and levies revenue in Semarang City. Samples taken of this study is taxes revenue data in fiscal year 2009-2012, levies revenue data in fiscal year 2009-2012, and local revenue data in fiscal year 2009-2012. Data collection technique used in this research is study documentation of the budget report. Analysis method used in this study was a quantitative descriptive analysis. The results showed that average growth of taxes 61.2%, the average growth of levies 6.89%. While the average contribution taxes 62.57%, the average contribution levies 19.44%. It is expected that the government could organize levies because it is low acceptance.Keywords: Taxes, Levies and Local Revenue